2008
DOI: 10.3892/ijo.33.1.49
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of combined immuno-chemotherapy with systemically administered gemcitabine and intra-portal administration of interleukin-2 in murine models of liver metastases of pancreatic cancer

Abstract: Abstract. Despite attempts to use multiple drug combinations that include gemcitabine (GEM), there is very little evidence that these combination regimens are superior to the single use of this agent. We therefore investigated the suppressive effect of the combination of systemically administered GEM and locally administered interleukin-2 (IL-2) on liver metastasis in pancreatic cancer. Tumor-bearing mice were randomly divided into four groups: a control group, an IL-2 intrasplenic (is) administration group, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Previous clinical trials in Japan targeted treatment of pancreatic cancer and hepatic metastases via direct portal vein has been attempted using either perfusion of 5-Fluorouracil 19 or injection of Gemcitabine alone 20 or in mouse tumor models, Gemcitabine in combination with IL-2 as an immunostimulatory agent 21 . These small pilot studies resulted in modest extension of progression free survival but added caution due to potentially high toxicity in the case of 5-FU 19 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous clinical trials in Japan targeted treatment of pancreatic cancer and hepatic metastases via direct portal vein has been attempted using either perfusion of 5-Fluorouracil 19 or injection of Gemcitabine alone 20 or in mouse tumor models, Gemcitabine in combination with IL-2 as an immunostimulatory agent 21 . These small pilot studies resulted in modest extension of progression free survival but added caution due to potentially high toxicity in the case of 5-FU 19 .…”
Section: Discussionmentioning
confidence: 99%
“…These small pilot studies resulted in modest extension of progression free survival but added caution due to potentially high toxicity in the case of 5-FU 19 . The mouse model studies indicated that immune stimulation improved the effectiveness of gemcitabine not only in tumor growth suppression but also through its inhibition of MDSC suppressor function in the tumor microenvironment 21 . Our MCR culture could provide a test platform to testbed more effective immune modulation therapies directed at breaking tumor supportive immune cell-CTC interactions in the portal circulation.…”
Section: Discussionmentioning
confidence: 99%
“…A luciferase expression vector (Gaussia luciferase pcDNA3) was stably transfected into AsPC-1 cells (AsPC-1-Luc) as described previously. After 1 week of acclimatization, mice underwent laparotomy involving a 2-cm horizontal incision under anesthesia with 3% isoflurane, as reported previously (23). The portal vein behind the pancreatic head was identified and exposed.…”
Section: Structural Formula and Appearance Of Dehydroxymethylepoxyqui...mentioning
confidence: 99%
“…A previous study revealed that proliferation of the human pancreatic cell line BxPC-3 was blocked by administration of the proteasome inhibitor PS-341, which indirectly blocks NF-ĸB activation (21). We previously reported that DHMEQ suppressed pancreatic cell carcinoma both in vitro and in vivo using subcutaneous (8), peritoneal (22) and liver metastasis models (9,23). However, DHMEQ displays poor solubility, and it was therefore administered intraperitoneally in these previous trials.…”
mentioning
confidence: 99%
“…More than 90% of deaths from cancer do not result from the primary tumor, but from the development of metastases (1).…”
Section: Introductionmentioning
confidence: 99%